2017
DOI: 10.1186/s12870-017-1174-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis of oil palm flowers reveals an EAR-motif-containing R2R3-MYB that modulates phenylpropene biosynthesis

Abstract: BackgroundOil palm is the most productive oil crop and the efficiency of pollination has a direct impact on the yield of oil. Pollination by wind can occur but maximal pollination is mediated by the weevil E. kamerunicus. These weevils complete their life cycle by feeding on male flowers. Attraction of weevils to oil palm flowers is due to the emission of methylchavicol by both male and female flowers. In search for male flowers, the weevils visit female flowers by accident due to methylchavicol fragrance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Clustering analysis of the R2R3-MYB gene family in A. thaliana revealed that the R2R3-MYB genes could be divided into 25 subfamilies ( Matus, Aquea & Arce-Johnson, 2009 ; Stracke, Werber & Weisshaar, 2001 ). Of all these subfamilies, the S4 subfamily was involved in the synthesis of various alkenes in Oil palm ( Li et al, 2017a ; Li et al, 2017b ). The S6 subfamily was proved to be closely related to the synthesis of carotenoids and anthocyanins ( Li et al, 2017a ; Li et al, 2017b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clustering analysis of the R2R3-MYB gene family in A. thaliana revealed that the R2R3-MYB genes could be divided into 25 subfamilies ( Matus, Aquea & Arce-Johnson, 2009 ; Stracke, Werber & Weisshaar, 2001 ). Of all these subfamilies, the S4 subfamily was involved in the synthesis of various alkenes in Oil palm ( Li et al, 2017a ; Li et al, 2017b ). The S6 subfamily was proved to be closely related to the synthesis of carotenoids and anthocyanins ( Li et al, 2017a ; Li et al, 2017b ).…”
Section: Introductionmentioning
confidence: 99%
“…Of all these subfamilies, the S4 subfamily was involved in the synthesis of various alkenes in Oil palm ( Li et al, 2017a ; Li et al, 2017b ). The S6 subfamily was proved to be closely related to the synthesis of carotenoids and anthocyanins ( Li et al, 2017a ; Li et al, 2017b ). The S7 subfamily was demonstrated to play a regulatory role in the terpenoid synthesis pathway in A. thaliana and M. spicata ( Reddy et al, 2017 ; Stracke et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of seeds due to the lack of endogenous hormones as a result of the expression change of the gene involved in the post-transcriptional products of the genes reduces the development of ovaries (Li et al, 2017) leads to small dates without seeds with low-quality features, also known as "Shees" (Khalil et al, 2021). Abd-Alaal et al…”
Section: Resultsmentioning
confidence: 99%
“…To compare the expression patterns of homologous genes, RNA sequencing reads of various organs from oil palm in our previous studies [31, 68, 69] and from date palm [70] were reanalyzed. Raw reads were cleaned with process_shortreads in Stacks package with default parameters, to remove adaptors and low-quality reads.…”
Section: Methodsmentioning
confidence: 99%